Relevansi Kebijakan Kenaikan Usia Pernikahan terhadap Kesiapan Berkeluarga: Analisis Pemikiran Prof. Nasaruddin Umar - Nila Fadllilatul Husna (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2025)
The amendment to the Indonesian Marriage Law through Law Number 16 of 2019, which raised the minimum marriage age to 19 years, was intended to strengthen child protection and promote marital readiness. Nevertheless, the policy has shown limited effectiveness in fostering substantive marriage readiness and long-term family resilience because it primarily emphasizes chronological age while paying insufficient attention to psychological, social, economic, and spiritual preparedness. This study aims to examine Prof. Nasaruddin Umar's concept of the